Right Ventricle Segmentation from Heart using Active Contour Model without Edge and Split Plane Decision - Chul Kang, Ho; ., . (International Journal of Engineering and Technology, 2018)
In this paper, we propose an automatic segmentation method of right ventricle from computed tomography angiography (CTA) using Chan-Vese model and split plane detection. First, we remove noise in the images by applying anisotropic diffusion filter and extract the whole heart using Otsu Thresholding. Second, the volume of interest (VOI) is detected by Chan-Vese model and morpholotical operation. Third, we divide the heart to left and right region using power watershed. Finally we detect split plane which divide right heart to right ventricle and atrium. We tested our method in ten CT images and they were obtained from a different patient. For the evaluation of the computational performance of the proposed method, we measured the total processing time. The average of total processing time, from first step to third step, was 13.92±1.28 s. We expect for our method to be used in cardiac diagnosis for cardiologist.
Keywords: Image segmentation; heart segmentation; right ventricle segmentation; Active Contour Model without edge; Chan-Vese model; split plane detection; power watershed